2018
DOI: 10.1063/1.5043095
|View full text |Cite
|
Sign up to set email alerts
|

Double-metal waveguide terahertz difference-frequency generation quantum cascade lasers with surface grating outcouplers

Abstract: We report terahertz quantum cascade laser (QCL) sources based on intra-cavity difference-frequency generation processed into double-metal waveguides with surface-grating outcouplers. This configuration enables high confinement of the terahertz mode in the device active region and efficient surface extraction of terahertz radiation along the entire length of the waveguide. The devices operate at room temperature at 1.9 THz and produce over 110 lW of peak power output with the mid-infrared-to-terahertz conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Finally, it is worth noting the spectral tunability of these devices. As it was already mentioned, room temperature THz difference-frequency generation scheme QCLs operates slightly below 2 THz [53], while conventional THz QCLs design at the highest reported temperature-250 K at 4 THz [49]. The issue to shift to lower frequencies the red wing in emission still remains unsolved and challenging; thus, probable alternative to cover subTHz frequencies can be electronic devices, like Schottky barrier-based frequency multipliers [56,57], CMOS technology-based oscillators [58][59][60][61][62], heterojunction bipolar transistors [63][64][65], or semiconductor superlattices [66][67][68].…”
Section: Thz Quantum Cascade Lasersmentioning
confidence: 82%
See 2 more Smart Citations
“…Finally, it is worth noting the spectral tunability of these devices. As it was already mentioned, room temperature THz difference-frequency generation scheme QCLs operates slightly below 2 THz [53], while conventional THz QCLs design at the highest reported temperature-250 K at 4 THz [49]. The issue to shift to lower frequencies the red wing in emission still remains unsolved and challenging; thus, probable alternative to cover subTHz frequencies can be electronic devices, like Schottky barrier-based frequency multipliers [56,57], CMOS technology-based oscillators [58][59][60][61][62], heterojunction bipolar transistors [63][64][65], or semiconductor superlattices [66][67][68].…”
Section: Thz Quantum Cascade Lasersmentioning
confidence: 82%
“…The peak powers, for instance, at 3.6 THz can be scaled up to 1.4 mW using the distributed-feedback waveguide withČerenkov phase-matching scheme [52]. THz QCLs processed into double-metal waveguides with surface-grating outcouplers allow to shift the red side of the emission below 2 THz and reach rather effective mid-infrared-to-terahertz conversion with peak power output over 110 µW at 1.9 THz [53].…”
Section: Thz Quantum Cascade Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve higher output power in the THz frequency, a more efficient THz extraction scheme is required since lower frequency THz generation is inherently difficult. Actually, recent studies have shown that the THz output of nonlinear THz-QCLs can be significantly improved by employing efficient THz out couplers [39,40].…”
mentioning
confidence: 99%
“…In addition, the temperature dependence of the device was investigated in a temperature range from 210 to 293 K, and stable single mode operation was achieved. In the near future, further improvements in performance may be achieved via the adoption of further efficient THz extraction schemes, 30,31) with the aim of producing THz sub-mW output power at room temperature. These high-performance THz NL-QCLs will open up new opportunities for many THz applications.…”
mentioning
confidence: 99%